Digital Book Teaching Materials Based on Local Wisdom to Improve Elementary School Student Literacy - Setyana Laspar Vianti; Joko Sulianto; Aryo Andri Nugroho (Mimbar Ilmu, 2026)
Daily classroom observations indicate that many elementary school students are still less active in learning activities, highlighting the need for teaching materials that can optimally enhance student engagement. This study aims to develop and evaluate a local wisdom based Digital Book teaching material to improve students’ literacy skills. The research employed a Research and Development (R&D) method using the ADDIE development model. The subjects of this study were fourth grade elementary school students with a one group pretest-posttest design. Data collection techniques included questionnaires, interviews, tests, and documentation, with instruments consisting of questionnaires and test items. Data analysis was conducted using N-Gain, t-test, and ANOVA.The results show that the developed teaching material is categorized as highly feasible and practical. The practicality test indicated very positive user responses. The t-test results revealed a significant difference between students’ learning outcomes before and after the implementation of the teaching material. Regression analysis showed that student activeness had a positive but not significant effect on literacy skills. These findings confirm that the local wisdom based Digital Book is valid, practical, and effective in improving students’ reading and writing literacy skills.The implication of this study is that the integration of local wisdom into digital teaching materials can serve as an innovative learning strategy that strengthens literacy development, enhances student engagement, and supports the transformation of technology based learning in elementary education.